Virtual Strategies for the Broad Delivery of High Intensity Exercise in Persons With Spinal Cord Injury: Ongoing Studies and Considerations for Implementation - McMillan, David W.; Astorino, Todd A.; Correa, Michael A.; Nash, Mark S.; Gater, David R. (Frontiers in Sports and Active Living, 2021)
Spinal cord injury (SCI) results in a multitude of metabolic co-morbidities that can be managed by exercise. As in the non-injured population, manipulation of exercise intensity likely allows for fruitful optimization of exercise interventions targeting metabolic health in persons with SCI. In this population, interventions employing circuit resistance training (CRT) exhibit significant improvements in outcomes including cardiorespiratory fitness, muscular strength, and blood lipids, and recent exploration of high intensity interval training (HIIT) suggests the potential of this strategy to enhance health and fitness. However, the neurological consequences of SCI result in safety considerations and constrain exercise approaches, resulting in the need for specialized exercise practitioners. Furthermore, transportation challenges, inaccessibility of exercise facilities, and other barriers limit the translation of high intensity ‘real world’ exercise strategies. Delivering exercise via online (“virtual”) platforms overcomes certain access barriers while allowing for broad distribution of high intensity exercise despite the limited number of population-specific exercise specialists. In this review, we initially discuss the need for ‘real world’ high intensity exercise strategies in persons with SCI. We then consider the advantages and logistics of using virtual platforms to broadly deliver high intensity exercise in this population. Safety and risk mitigation are considered first followed by identifying strategies and technologies for delivery and monitoring of virtual high intensity exercise. Throughout the review, we discuss approaches from previous and ongoing trials and conclude by giving considerations for future efforts in this area.